El uso de los puzzles en el desarrollo cognitivo en niños de inicial II de la Unidad Educativa Fiscomisional “Dr. Gabriel García Moreno” del cantón Guano - Allauca Tierra, Janire (2024)
Education is constantly changing and adapting, and we seek to improve the teachinglearning process, starting from the youngest. The present research entitled The use of puzzles in cognitive development in children of Initial II of the Fiscomisional Educational Unit "Dr. Gabriel García Moreno" of the Guano canton has as its general objective to determine the frequency of the use of puzzles as a methodological strategy for cognitive development in children of Initial II in the institution above. To achieve this purpose, a methodology with a mixed approach has been used, using a non-experimental design and a bibliographical level. In this way, it was configured as a field study, which allowed reliable data to be obtained from the actual context of the institution. The observation technique was used to get the data, focusing on how puzzles of different materials strengthen cognitive development. To do this, an observation sheet was prepared with specific indicators, which allowed the evaluation of children's different attitudes and development about the subject of study. The results obtained through observation revealed that puzzles have been a method of distraction but not a teaching tool for cognitive development. Based on the analysis of the results, a set of strategies has been developed so that teachers can apply it. It is important to highlight that this research contributed greatly to the educational and social field by providing recommendations that can be very useful in the cognitive development of children as well as guaranteeing a quality education.